Pathophysiology of outer retinal corrugations: Imaging dataset and mechanical models - Isabela Martins Melo; Masoud Nourouzi Darabad; Arun Ramachandran; Paola Lourdes Oquendo; Hesham Hamli; Wei Wei Lee; Flavia Nagel; Aditya Bansal; Rajeev H. Muni (Data in Brief, 2023)
This article presents high-resolution swept-source optical coherence tomography (SS-OCT) imaging data used to elaborate a mechanical model that elucidates the formation of outer retinal corrugations (ORCs) in rhegmatogenous retinal detachments (RRD). The imaging data shared in the repository and presented in this article is related to the research paper entitled “Outer Retinal Corrugations in Rhegmatogenous Retinal Detachment: The Retinal Pigment Epithelium-Photoreceptor Dysregulation Theory” (Muni et al., AJO, 2022). The dataset consists of 69 baseline cross-sectional SS-OCT scans from 66 patients that were assessed for the presence of ORCs and analyzed considering the clinical features of each case. From the 66 cases, we selected SS-OCT images of 4 RRD patients with visible ORCs and no cystoid macular edema (CME) to validate the mechanical model. We modelled the retina as a composite material consisting of the outer retinal layer (photoreceptor layer) and the inner retinal layer (the part of the retina that excludes the photoreceptor layer) with thicknesses To and Ti and elastic modulus Eo and Ei, respectively. The thickness of the outer and inner retinal layers and the relative increase in the length of the outer retinal layer (γ) were measured from the SS-OCT images. Measurements from the SS-OCT images of patients with RRD demonstrated a 30% increase (γ=0.3) in the length of the outer retinal layer and a 400% increase in the thickness of the outer retinal layer (To). Using the mathematical model, Eo/Ei ranged between 0.05 to 0.5 to result in ORCs with a similar frequency to those observed in the SS-OCT scans.